2000
DOI: 10.1029/1999gl010799
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of SO2 above northern Greece

Abstract: Abstract. This paper describes the sources contributing to two seasonal peaks in colunmar SO2 amounts measured with a Brewer spectrophotometer at Thessaloniki, Northern Greece since 1982. The SO2 Brewer measurements combined with those at ground level, meteorological analysis and numerical simulations provide estimates on the contribution of local and remote sources to the SO2 column. It is shown that more than 50% of the observed SO2 column can be attributed to ligniteburning sources in Bulgaria, Romania and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 5 publications
5
41
0
8
Order By: Relevance
“…Central Europe is identified as by far the most important emitting region for both SO 2 and nss-SO 4 measured in Crete. The Central Europe source strength of S compounds calculated here is in agreement with previous findings of Zerefos et al (2000) who reported that 70% of SO 2 measured North of Greece (Thessaloniki) originates in Bulgaria and surrounding countries. Important sources were observed from Hungaria, Romania and Bulgaria, which is in agreement with SO 2 emission data for 1999 provided by UNECE/EMEP.…”
Section: So 2 and Nss-so 4 Sourcessupporting
confidence: 82%
See 2 more Smart Citations
“…Central Europe is identified as by far the most important emitting region for both SO 2 and nss-SO 4 measured in Crete. The Central Europe source strength of S compounds calculated here is in agreement with previous findings of Zerefos et al (2000) who reported that 70% of SO 2 measured North of Greece (Thessaloniki) originates in Bulgaria and surrounding countries. Important sources were observed from Hungaria, Romania and Bulgaria, which is in agreement with SO 2 emission data for 1999 provided by UNECE/EMEP.…”
Section: So 2 and Nss-so 4 Sourcessupporting
confidence: 82%
“…Another explanation could be that numerous power plants in Central Europe S-containing lignite as fossil fuel inject SO 2 at up to several hundred meters altitude, even reaching the lower free troposphere. Evidence for this theory has recently been gathered in the form of SO 2 maxima frequently observed at the top of the PBL over northern Greece (Zerefos et al, 2000 and references herein; P. Formenti, personal communication). This phenomenon is likely to result in higher long-range transport of this compound.…”
Section: So 2 Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hypothesis relayed on a possible contribution of the thermal power station to the global concentration of SO 2 in Beirut. (Lelieveld et al 2002;Luria et al 1996;Sciare et al 2003;Zerefos et al 2000). Since the lifetime of SO 2 varies from a few days to weeks (Wayne 2000), the HYSPLIT model was used to establish the 48-h backward trajectories of air masses ending in Beirut for the whole period of the measurements.…”
Section: Periods and Sampling Sitesmentioning
confidence: 99%
“…Apart from local pollution, aerosols that originate from biomass burning, anthropogenic aerosols from the highly populated urban centres and industrial areas of Central and Eastern Europe and maritime aerosols, converge over this area (Formenti et al, 2002;Balis et al, 2003). For the lower troposphere over the Mediterranean, particularly during summer, European pollution is mainly responsible for the reduction of air quality, whereas in the free troposphere pollution is largely determined by trans-boundary and possibly intercontinental transport (Zerefos et al, 2000;Lelieveld et al, 2002;Balis et al, 2003Balis et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%